2007
DOI: 10.1007/s10823-006-9025-z
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Trends in Functional Limitation and Disability Among Older Asians: A Comparison of Five Asian Settings

Abstract: The objective of this paper is to examine short-term trends in the prevalence of limitation in Activities of Daily Living (ADL), Instrumental Activities of Daily Living (IADL) and Nagi physical functioning tasks among persons age 60 years or older in five Asian settings: Indonesia, the Philippines, Singapore, Taiwan and the Beijing Municipality. The data come from recent panel surveys of older adults that span a period of 3-4 years during the mid to late 1990s. Results suggest a general trend toward an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…Nagi's tasks for physical functioning typically include standing for 15 min, crouching, squatting, kneeling, stooping, raising one's hands overhead, grasping with fingers, lifting a heavy object, climbing stairs, walking 200-300 m, walking five kilometers, and standing up from a chair Martin et al 2011;Nagi 1965;Ofstedal, et al 2007). …”
Section: Common Disability Measures In Aging Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Nagi's tasks for physical functioning typically include standing for 15 min, crouching, squatting, kneeling, stooping, raising one's hands overhead, grasping with fingers, lifting a heavy object, climbing stairs, walking 200-300 m, walking five kilometers, and standing up from a chair Martin et al 2011;Nagi 1965;Ofstedal, et al 2007). …”
Section: Common Disability Measures In Aging Researchmentioning
confidence: 99%
“…We assumed a linear change and both sexes shared the same trend. (h) The trends in ADL disability for China in the 1990s was from Gu and Zeng (2006) and Gu et al (2009 Indonesia and the Philippines in the 1990s (Ofstedal et al 2007) and even reversed in Thailand after 2005 (Karcharnubarn 2010). Although we are unable to identify IADL trends for many countries, existing data suggest that trends in IADL disability were more or less similar to trends in ADL disability in most countries/areas.…”
Section: Empirical Evidence Of Overall Trends In Disabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…5 Against this backdrop, the discourse on challenges of ageing and health in SSA centres not, as it does in industrialized countries, on queries about expected trends in old age morbidity, mortality and disability and the sustainability of existing health and care systems. [6][7][8] The focus, rather, are concerns about a heightened vulnerability of older persons to detrimental health outcomes -in two respects. On one level, older populations in SSA are deemed to be at particularly high risk of ill-health and disability from age-related chronic non-communicable disease (CNCD), due to a lifetime of exposure to conditions of deprivation and a growing prevalence of modifiable CNCD risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Global effort in collecting time series data on risk behaviors at the country or sub-national levels is necessary. Fifth, studies have shown that health conditions among several elderly populations in the region is getting worse, in spite of prolonged longevity (Cheung and Yip 2010;Ofstedal et al 2007). Yet we are unable to examine possible trajectories of health expectancies (Robine and Michel 2004) primarily because of space limitations and lack of nationwide data.…”
Section: Discussionmentioning
confidence: 99%